PENGARUH EFEKTIFITAS PENGENDALIAN INTERNAL, KESESUAIAN KOMPENSASI, DAN MORALITAS INDIVIDU TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Kasus Pada PT. POS Indonesia KCU Kota Pekanbaru) - Tia Radhiah; Raja Adri Satriawan S.; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this research is to find out the effectiveness of internal control, compensation compatibility and individual morality on accounting fraud tendency. Data for this study was obtained from samples of all supervisors, managers and the managers assistants whose working at the PT POS Indonesia Pekanbaru main branch office. This research is using survey methods by delivering the questioner instrument directly to PT POS Indonesia Pekanbaru main branch office. Total respondents which is used in this research are 53 respondents (89.84%). The analyzing method used in this research is Double Regression methods using SPSS (Statistical Product and Service Solution) version 20. Result of the study indicates that the effectiveness of internal control, compensation compability and individual morality influencing accounting fraud tendency. All of the independent variables jointly influence dependent variables as much as 76.2%, while 23.8% is influenced by other unclear variable.Keywords : Effectivity, Compensation, Morality, Fraud, and Accountancy.